2016
DOI: 10.3389/fnana.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroanatomical Basis for Posterior Superior Parietal Lobule Control Lateralization of Visuospatial Attention

Abstract: The right hemispheric dominance in visuospatial attention in human brain has been well established. Converging evidence has documented that ventral posterior parietal cortex (PPC) plays an important role in visuospatial attention. The role of dorsal PPC subregions, especially the superior parietal lobule (SPL) in visuospatial attention is still controversial. In the current study, we used repetitive transcranial magnetic stimulation (rTMS) and diffusion magnetic resonance imaging (MRI) techniques to test the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 58 publications
4
44
0
Order By: Relevance
“…The behavioral domain and paradigm analyses of the IPL subregions revealed that Cl3 primarily participated in inhibition and attention and suggested that Cl3 in the RIPL plays a key role in attention reorientation. Our finding was supported by previous anatomical connectivity analyses, which revealed that the betweenhemispheric asymmetry of the anatomical connections of the IPL with the middle and inferior frontal gyri underlies the lateralization of visuospatial attention [Thiebaut de Schotten et al, 2011;Wu et al, 2016].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The behavioral domain and paradigm analyses of the IPL subregions revealed that Cl3 primarily participated in inhibition and attention and suggested that Cl3 in the RIPL plays a key role in attention reorientation. Our finding was supported by previous anatomical connectivity analyses, which revealed that the betweenhemispheric asymmetry of the anatomical connections of the IPL with the middle and inferior frontal gyri underlies the lateralization of visuospatial attention [Thiebaut de Schotten et al, 2011;Wu et al, 2016].…”
Section: Discussionsupporting
confidence: 89%
“…More recently, Mars et al [2012] used an anatomical connectivity-based parcellation approach to parcellate the right temporoparietal junction (TPJ) including the IPL, and found that the anterior TPJ, not the IPL that we found, primarily participated in the attention network. Our finding was supported by previous anatomical connectivity analyses, which revealed that the betweenhemispheric asymmetry of the anatomical connections of the IPL with the middle and inferior frontal gyri underlies the lateralization of visuospatial attention [Thiebaut de Schotten et al, 2011;Wu et al, 2016]. The taskbased fMRI detected the functional activation and revealed the approximately anatomical location.…”
Section: Discussionsupporting
confidence: 88%
“…The sPar is part of a dorsal processing stream that is related to attention and associated with performance on experimental tasks measuring various cognitive domains, including attention and memory (Kumfor et al, 2015; Rosen et al, 2015). For example, the sPar was found to mediate visuospatial attention in a recent transcranial magnetic stimulation study (Wu et al, 2016). The mPFC, on the other hand, is part of the default-mode network and decreased activity in that network is consistent with a shift to a more attention-focused brain state (Raichle and Snyder, 2007; Wang and Li, 2013).…”
Section: 0 Discussionmentioning
confidence: 99%
“…The predominant MD abnormalities in the right hemisphere fits well with impaired visuo-spatial ability (Vogel, Bowers, & Vogel 2003;Wu et al, 2016) and social cognition (De Pisapia et al, 2014;Mitchell & Phillips, 2015). The predominant MD abnormalities in the right hemisphere fits well with impaired visuo-spatial ability (Vogel, Bowers, & Vogel 2003;Wu et al, 2016) and social cognition (De Pisapia et al, 2014;Mitchell & Phillips, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…These microstructural abnormalities are in line with the cognitive phenotype of NF1 patients. The predominant MD abnormalities in the right hemisphere fits well with impaired visuo-spatial ability (Vogel, Bowers, & Vogel 2003;Wu et al, 2016) and social cognition (De Pisapia et al, 2014;Mitchell & Phillips, 2015). Impairment of the thalamus and of its projections on the visual and frontal cortex may contribute to the executive and/or the visuo-spatial deficits in NF1.…”
Section: Discussionmentioning
confidence: 67%